The Influence Of Elderly Gymnastics On Mother Anxiety At Sanggulan Health Centre - Dwi Hartati; iin Safitri (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2021)
The purpose of this study was to find out the effect of elderly exercise on the anxiety of climacteric mothers at the Sanggulan Village Support Health Center . This study This type of quasy experimental research with the research design is a one group pretest- posttest design. Total sample of 38 respondents using accidental sampling method. Result the Wilcoxon statistical test in the SPSS program obtained a value of p = 0.000, meaning that there was a difference between the results of the pre-test and post-test. There is an influence between elderly gymnastics and maternal climacteric anxiety